Anti Inflammatory Potential of Moringa Oleifera Lam. Bark In Jaipur Region - Chauhan, Nidhi; Sharma, Vandana; Pareek, Ramesh; Kushwaha, Ashish (Asian Journal of Pharmaceutical Research and Development, 2021)
Objective: To investigate the anti-inflammatory potential of moringa oleifera lam. (M.Oleifera L.) bark crude ethanolic extract in regards to phytochemical studies . Method: compared tha anti-inflammatory effect of M.Oleifera L. at (300, 200 and 100 mg/kg, p.o) doses with that of standard anti-inflammatory agent like diclofenac sodium at a dose of (10mg/kg, p.o) using carrageenan induced paw edema and egg albumin induced paw edema. Result: Hydroalcoholic extract of M.Oleifera L. stem bark at a dose of 300mg/kg p.o and 200mg/kg p.o showed a significant dose dependent as campare to 100mg/kg, further it was compared with the reduction of paw edema against standard drug diclofenac sodium at a dose of 10mg/kg p.o both in carrageenan induced and egg albumin induced paw edema. The decrease in the edema volume was seen over a period of time from 2nd, 3rd, and 4thhour where the degree of edema was reduce. Conclusion: from the above findings it was observed that the hydroalcoholic extract of M.Oleifera L.possess a significant anti-inflammatory activity against the animal model.